MARKETING CONTENT INSTAGRAM SEBAGAI MEDIA PROMOSI PADA PT POS INDONESIA (PERSERO) KCU MAKASSAR 90000 - Setianingsih, Ayu; Murtafia, Murtafia (ADMIT: Jurnal Administrasi Terapan, 2023)
The objective of the study was to create marketing content in the form of promotional videos based on drama stories used as a promotional strategy at KCU Pos Makassar 90000. This study applied qualitative descriptive approach. The data collected through document review and semi-structured interviews with a variety of stakeholders who can aid researchers in the study process. According to the findings of this study, the sales promotion indicators employed are promotional media, promotion time, frequency, promotion quality, quantity, and determination or compliance of promotional aims. Furthermore, it employs marketing content elements to be considered dependable, notably relevancy, informativeness, dependability, value, distinctiveness, emotions, and intelligence. As a result of this study, the KCU Pos Makassar 90000 Instagram account now has marketing content in the form of movies with drama plots that are used as promotional media. Marketing content in the form of videos with drama narratives is projected to be an effective promotional medium for introducing products and services at KCU Pos Makassar 90000 and can serve as a content reference for businesses.